2021
DOI: 10.1257/pol.20180674
|View full text |Cite
|
Sign up to set email alerts
|

Do School Spending Cuts Matter? Evidence from the Great Recession

Abstract: During the Great Recession, national public school per-pupil spending fell by roughly 7 percent and persisted beyond the recovery. The impact of such large and sustained education funding cuts is not well understood. To examine this, first, we document that the recessionary drop in spending coincided with the end of decades-long national growth in both test scores and college-going. Next, we show that this stalled educational progress was particularly pronounced in states that experienced larger recessionary b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(53 citation statements)
references
References 31 publications
3
50
0
Order By: Relevance
“…Two recent survey articles summarized the newer literature with similar findings for the average effect of spending across studies (Handel & Hanushek, 2023; Jackson & Mackevicius, in press). They found that changes in spending are, on average, related to small positive impacts on student test scores and attainment.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Two recent survey articles summarized the newer literature with similar findings for the average effect of spending across studies (Handel & Hanushek, 2023; Jackson & Mackevicius, in press). They found that changes in spending are, on average, related to small positive impacts on student test scores and attainment.…”
Section: Introductionmentioning
confidence: 82%
“…Jackson and Mackevicius (in press) harmonized effects across a sample of studies and used meta‐analytic methods to estimate universal marginal impacts of generalized spending on test scores and attainment. They used their estimates to predict potential future impacts in other contexts.…”
Section: Where Does That Leave the Education Spending Debate?mentioning
confidence: 99%
“…These benefits were discernibly greater for students from poor families. Jackson et al (2021) also found that exposure to $1,000 per-pupil spending cuts during the Great Recession resulted in about 0.04 SD lower test scores and declining college-going rates.…”
Section: Does Finance Reform Alter School Organizations?mentioning
confidence: 90%
“…For instance, districts may use ESSER funds more efficiently than funds exogenously introduced via a school finance reform. Indeed, Jackson and colleagues (2021) conclude that districts appear to be more efficient with resources during recessionary periods, as the negative fiscal shock from the Great Recession reduced achievement less in an absolute sense relative to equivalent positive fiscal shocks. Of course, districts may also use ESSER funds less efficiently if, for example, they cannot hire supplemental staff due to labor market constraints or do not recognize the severity of lost learning that occurred during the pandemic.…”
Section: Were Federal Funds Sufficient To Meet Policy Goals?mentioning
confidence: 99%
“…The Great Recession inflicted significant long-term damage to the US economy and to P–12 revenues specifically, driven primarily through declines in state revenue (Leachman et al, 2017). By some estimates, school spending declined by seven percent nationally (Jackson et al, 2021), equivalent to $945 per pupil per year for 6 years (Anglum et al, 2021), with nearly 300,000 school employees laid off (Evans et al, 2019). These losses in resources caused student achievement to decline, especially in areas with the largest employment losses and among districts serving predominantly economically disadvantaged and minority students (Shores & Steinberg, 2019a; Jackson et al, 2021).…”
Section: Background On Federal Fiscal Stimulus During the Great Reces...mentioning
confidence: 99%